Mary, Mothers, Lament, and Feminist Theology: The Dead Non-War Heroes of Nagasaki - McClelland, Gwyn (Journal of feminist studies in religion, 2020)
In this essay, McClelland introduces some reflections of Nagasaki atomic bomb survivors about the loss of their mothers and some of their experiences of motherhood in the aftermath, utilizing a feminist lens to analyze the effects of the bomb. Japanese feminist Chizuko Ueno has written that those women who died might be signified as "non-war heroes" in an East Asian context where the "war-heroes" are traditionally male. The author draws on Kwok Pui-Lan's postcolonial theology of religious difference and Shelly Rambo's mixed terrain of remembering to discuss how and to what degree the violence and rupture of the atomic bombing is contested in the memory of the survivors. McClelland describes how the narratives of the Catholic survivors contain a common thread about Mary, whom they implicitly perceive as an expression of a "female face of God." The interviews considered here were collected between 2014 and 2016 as part of a larger historical project that employed a theological lens in describing the interpretation of Catholic memory of the atomic bombing of Nagasaki.